Marawi State University- Information and Communications Technology: Its Vital Role in Teacher Education Program in the Autonomous Region in Muslim Mindanao - Abdulcader M. Ayo (JPAIR Institutional Research Journal)
The higher education system is a critical factor that influences the overall prosperity of a nation. The remarkable growth in the higher education sector leads to a diversified administration of higher education institutions (HEIs). The study assessed the: 1) school facilities, 2) training program, 3) number of graduated students by course, and 4) projects implemented. Using descriptive design involving qualitative research techniques, the researcher employed documentary analysis including annual reports, CHED Memoranda, special orders, bulletins found in the library and other relevant materials from the Office of Vice Chancellor for Academic Affairs. Personal interviews were conducted with key university officials involved in the implementation of ICT programs. Findings revealed that the effective implementation of ICT programs greatly depends on the interest, commitment and the presence of effective school leadership in the program. ICT programs like curriculum and managerial skills should be incorporated into the training of school leaders among its University campuses. The study developed an action plan program which includes: 1) developing a module which will serve as a reference for faculty and students; and 2) conducting a series of training program among secondary high school principals/faculty and students of the MSU-Community High Schools on the effective usage of computers, Laptop Computers, LCD Projectors and the Internet in their day-to-day work.